APLIKASI ENKRIPSI DAN DEKRIPSI DATA GAMBAR MENGGUNAKAN ALGORITMA ADVANCED ENCRYPTION STANDARD - Rabiu, Muh Fajril; husdi; Dalai, Hastuti (Jurnal Ilmiah Ilmu Komputer Banthayo Lo Komputer, 2025)
Digital data security is becoming increasingly important in today's information age, including image data protection. This research aims to develop an image data encryption and decryption application using the Advanced Encryption Standard (AES) algorithm to improve data security. To further strengthen the security of private keys, the RSA algorithm is used in securing the private keys used in the encryption and decryption process. The application of the AES algorithm on image data shows that this method effectively maintains data confidentiality and integrity. The research results confirm that the AES algorithm can be effectively applied for image data security. The RSA algorithm used to secure the private key is performed to strengthen the security, making it more difficult for cryptanalysts to obtain the private key from the AES algorithm used. Application testing is conducted using White-Box and Base Path methods which resulted in a value of V(G) = CC = 6, indicating well-managed complexity. In addition, Black-Box testing shows the correctness of the application logic, proving that the logic flowchart used in the application is correct and reliable. It means that the application developed can be operated effectively and, in practice, is feasible to protect image data from security threats.